Aplicación de Kahoot como herramienta educativa para la enseñanza - Machaca-Huamanhorcco, Elsa (2022)
The research allowed demonstrating the effect of the Kahoot tool in the development of the competence constructs historical interpretations in second year high school students of an educational institution of the Socabaya district located in the Arequipa region. The study corresponds to a quantitative approach of quasi-experimental design applied to a sample of 52 students. The results of the research showed that after the application of Kahoot, the effects in the experimental group showed statistically significant differences, since most students were at the satisfactory achievement level, with a considerable decrease in the number of students at the level prior to the start and at the beginning; on the other hand, the control group maintained almost homogeneous results from one level to another.